Study of the performance of oil fuel burner using burner insert - 286791 Farida Tufail Ahmad (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper ((Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2006